Schistosoma haematobium bilharziasis during overwintering in Adelie land: Health and operational risk in Antarctica - A. Buguet (Health Risk Analysis, 2022)
While serving from December 1970 to January 1972 as a medical doctor of the 21st French Polar Expedition in Adelie Land, Antarctica, at Dumont d’Urville Station, the author diagnosed Schistosoma haematobiumurinary bilharziasis in a winterer who suffered from pain in the right iliac fossa, at the beginning of the overwintering. The patient had participated in a bush investigation in West Africa, but, despite his complaints, the illness had not been diagnosed prior to the Antarctic expedition. Microscopic examination revealed Schistosoma haematobium eggs in the urine centrifugation deposit. In the absence of anti-bilharziasis medication, the patient was treated symptomatically with urinary antiseptic or antibiotic, hemostatic and antihistamine medications to palliate the egg deposition in the bladder wall and the subsequent induction of inflammatory reactions. Nine months later, a US Navy plane landed on the continent in the vicinity of the French Station and delivered the specific parasiticidal niridazole tablets. The patient received three niridazole tablets per day during one week. He returned to Paris in March 1972. Exploratory medical tests did not reveal any bladder or urinary tract alteration. He never since complained of any related problem. Recommendations are provided to avoid personal and / or operational risks due to such tropical infectious diseases during Antarctic expeditions.